2011
DOI: 10.4269/ajtmh.2011.10-0583
|View full text |Cite
|
Sign up to set email alerts
|

Infection Prevalences of Common Tick-borne Pathogens in Adult Lone Star Ticks (Amblyomma americanum) and American Dog Ticks (Dermacentor variabilis) in Kentucky

Abstract: Abstract. Rocky Mountain spotted fever, Lyme disease, and ehrlichiosis are tick-borne diseases that are reported annually in Kentucky. We conducted a survey to describe infection prevalence of tick-borne pathogens in Amblyomma americanum and Dermacentor variabilis ticks collected in Kentucky. During 2007-2008, we collected 287 ticks (179 D. variabilis and 108 A. americanum ) from canine, feral hog, horse, raccoon, white-tailed deer, and human hosts in six counties in Kentucky. Ticks were screened for Rickettsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 56 publications
4
35
0
1
Order By: Relevance
“…R. parkeri is distributed throughout multiple tissues of infected A. maculatum ticks, including the salivary glands, the midgut, the Malpighian tubules, and the ovaries (102). R. parkeri is detected infrequently in A. americanum (103) and D. variabilis (79,104). Infections of dogs and cows caused by R. parkeri have been reported in the southeastern United States (105,106).…”
Section: North and Central Americamentioning
confidence: 99%
See 2 more Smart Citations
“…R. parkeri is distributed throughout multiple tissues of infected A. maculatum ticks, including the salivary glands, the midgut, the Malpighian tubules, and the ovaries (102). R. parkeri is detected infrequently in A. americanum (103) and D. variabilis (79,104). Infections of dogs and cows caused by R. parkeri have been reported in the southeastern United States (105,106).…”
Section: North and Central Americamentioning
confidence: 99%
“…Contemporary molecular surveys for R. rickettsii in North American Dermacentor ticks reveal extremely low frequencies of occurrence of these bacteria in ticks, characteristically Ͻ0.5% (76)(77)(78)(79)(80). However, unusually large numbers of R. rickettsii-infected Rhipicephalus sanguineus ticks are a hallmark of several hyperendemic foci of RMSF in the United States and Mexico (54,56,(81)(82)(83), suggesting that Rhipicephalus sanguineus may be a more important vector of RMSF in North and Central America than previously recognized.…”
Section: North and Central Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous tick surveys, including those conducted in Tennessee, have shown the absence of R. rickettsii but the presence of other SFG Rickettsia such as Rickettsia amblyommii, Rickettsia Parkeri, and Rickettsia montanensis. [5][6][7][8][9][10] The contradicting reports of increasing incidence of SFG rickettsiosis (including RMSF) and the rarity of R. rickettsii in ticks raise the likelihood that other SFG rickettsiae species are contributing to this increase in incidence. Previous studies have demonstrated evidence for infection with other less pathogenic SFG rickettsiae species that clinically resemble RMSF.…”
Section: Introductionmentioning
confidence: 78%
“…17,20,[34][35][36][37][38][39][40][41][42][43][44] Because of these large differences in prevalence, exposure to R. rickettsii may be rare relative to exposure to "Ca. Rickettsia amblyommii".…”
Section: Discussionmentioning
confidence: 99%